Makar/Bughat Ditinjau Dari Fiqh Siyasah - Noviansyah, Noviansyah; Siregar, Dame (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Treason is a criminal act related to domestic state security issues. Master of criminal acts that may danger the interest of the community and the state. Our expert may disturb the national stability. In history Indonesia has been some times expected by the citizens of its citizens. Expert action is conducted concerning the ideology of the nation, so that make a assessment to the ruled head of the state. Criminals that enter into the category of treason that threaten state security and the safety of the republic of indonesia are contained in chapter i book ii of the criminal code form of article 104, which is examinations attracting the president's security, while in islamic criminal law of reviews including the huddudjuly in conditions and conditions qur'ansurat al-hujurat verse 9.Is there a solution to the problem in this research, what is the punishment of the makers of the makar against kuhp article 104? And how does fiqhsiyasah review against attractors in kuhp article 104?.This research is a descriptive analitical and normative descriptive qualitative research, because the source of data cannot be separated with library data, between other substitutes, journals, subject examinations, subject examinations, subject examinations, subject examinations.In this research finding the results that expert sanctions in islamic law are conflict and a death penalty (jarimah huddud), and sanctions for expert persons according to positive law is a criminal prison. However this is a criminal expert expert can already be criminal if have meeted three elements, that is the beginning of intention, the beginning of the implementation and the implementation is not completed because of his own will, and is understanded. However, in the provision of sanctions to bughat or expert must be careful and previously there must be a musyawarah process.